2015
DOI: 10.1080/07481187.2015.1037971
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Investigation of Suicidal Disclosures and Attitudes in Austrian and Turkish University Students

Abstract: The prevalence of suicidal behavior and the nature of attitudes toward suicide differ in Austria and Turkey. To see if there were differences in disclosure, 351 Turkish and 310 Austrian students answered questions about disclosing suicidal thoughts. More Austrian than Turkish students reported suicidal ideation and believed that suicidal people disclose their plans, but suicidal disclosures were equally common in the two groups. Compared to Austria, suicidal disclosures in Turkey met with more positive social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…This finding is inconsistent with the cross-cultural studies by Eskin and colleagues (Eskin, 1999;Eskin, Palova, & Krokavcova, 2014;Eskin, Schild, Oncu, Stieger, & Voracek, 2015) suggesting the presence of more accepting and helping reactions to suicide disclosures among Turkish young adults compared to a number of European populations (Slovakia, Switzerland, Austria). These contradictory findings could be explained by the differences in research design between the current bottom-up (qualitative) research and the survey design that was used by Eskin and colleagues.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is inconsistent with the cross-cultural studies by Eskin and colleagues (Eskin, 1999;Eskin, Palova, & Krokavcova, 2014;Eskin, Schild, Oncu, Stieger, & Voracek, 2015) suggesting the presence of more accepting and helping reactions to suicide disclosures among Turkish young adults compared to a number of European populations (Slovakia, Switzerland, Austria). These contradictory findings could be explained by the differences in research design between the current bottom-up (qualitative) research and the survey design that was used by Eskin and colleagues.…”
Section: Discussioncontrasting
confidence: 57%
“…To our knowledge, the most in‐depth study of suicidal ideation disclosure patterns to date was conducted by Eskin and colleagues (). This study examined experiences with disclosure among 351 Turkish and 310 Austrian medicine and psychology students (29.9% and 45.9%, respectively, reported a lifetime history of suicidal thoughts).…”
Section: The Present Studymentioning
confidence: 99%
“…However, Turkish adolescents and young adults were more accepting of an imagined suicidal close friend than counterparts in other groups. In line with this, Eskin, Schild, Öncü, Stieger and Voracek () showed that although frequencies of suicidal disclosures were the same in Austrian and Turkish groups, Turkish students disclosed their suicidality to more people than the Austrian, and suicidal disclosures in Turkey were met with helping social reactions more frequently than suicidal disclosures in Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Second, an individual in need of support should make her/his need clear to others. Third, the culture in which the social support process takes place must facilitate the availability of those who are giving and the behavioral initiations of both the receiver and the giver (Eskin et al ., ).…”
Section: Introductionmentioning
confidence: 99%